Talent recognition and development - Elaborating on a principle model - Krasilshchikov, O. (International Journal of Developmental Sport Management, 2011)
Correctly adjusted system of Talent Identification is often regarded as the first step to international success. Talent identification, orientation within wide variety of sports and events, and further selection is a complex multidimensional process. Purpose of the study was to scrutinize the systems of Talent Identification and Development available worldwide and to suggest the one fitting the sports development scenario of the countries with limited human resources. Methods of the study included examination and evaluation of the available literature and systems of talent identification and development existing in the world`s leading sporting nations. Thorough analysis of talent identification and development approaches from around the world has brought out number of special features either to follow or to dismiss. Ultimately, besides other important factors determining the approaches to Talent Identification, one kept overweighing all others by drastically changing the process. That one was: availability or absence of human resources to pick the talent from. Countries with limited human potential might need to develop their own versions of Talent Identification generally based on the erstwhile GDR principle model; however the present study instead of narrowing the process to Talent Detection and Talent Identification only has suggested a five-component Talent Recognition system effective throughout the long term preparation in sports. It is also suggested to pay more attention to Pre-Talent Identification Talent Development, not to just PostTalent Identification Talent Development alone. In Post-Talent Identification Talent Development practical aspect of Talent Handling are addressed and within Talent Development it is suggested to pay special attention to Talent Migration / Transfer and to Talent Retention / Recycling.